Having a prevention regulatory focus longitudinally predicted distress and health‐protective behaviors during the COVID‐19 pandemic - Rodrigues, D. L. (2022)
People focused on prevention (vs. promotion) are motivated by safety and are less inclined to take risks. We tested if having a prevention (vs. promotion) focus before the COVID-19 pandemic outbreak predicted threat perceptions and health outcomes throughout the pandemic. Participants (N = 161) took part in a longitudinal study. Measures were assessed before the pandemic was declared (on November 2019, T1) and after a global pandemic was declared (on June 2020, T2). Participants who were more focused on prevention prior to the onset of the pandemic (at T1) perceived greater risk and were more worried about contracting COVID-19 and engaged in more preventive behaviors during the pandemic (at T2). They also reported less anxiety and felt healthier (at T2). Exploratory analyses revealed that enacting preventive behaviors helped people cope with pandemic-related anxiety. Being motivated by security and enacting preventive behaviors seems to have helped people reduce anxiety over risk even during the pandemic.